PANI-ZnO Cladding-Modified Optical Fiber Biosensor for Urea Sensing Based on Evanescent Wave Absorption - Botewad, S. N.; Pahurkar, V. G.; Muley, G. G.; Gaikwad, D. K.; Bodkhe, Gajanan A.; Shirsat, Mahendra D.; Pawar, P. P. (Frontiers in Materials, 2020)
In present investigation, we demonstrated a simple, rapid and highly sensitive cladding modified optical fiber urea sensor based on evanescent wave absorption (EWA) technique. Cladding modification was exploited over 2 cm unclad portion of optical fiber using polyaniline-zinc oxide (PANI-ZnO) matrix and enzyme-Urease (Urs) cross-linked on it via glutarldehyde as a cross-linking agent. PANI-ZnO matrix was characterized by X-ray diffraction, scanning electron microscopy, ultraviolet-visible and Fourier transforms infrared spectroscopy to explore the various properties. The developed sensor shows the linear response in the range 10 nM - 1M towards urea concentration in form of absorption spectra at wavelength 250 nm with specific selectivity. Under the proper condition (store at temperature 40 C after the each measurement) shows 40 days stability without any decrement in intensity of absorption spectrum. Thus, the developed sensor is highly sensitive, stable and specific selective with 10 nM lower detection limit of urea concentration.